Animal production in warm climates - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Animal production in the tropics and subtropics by Jean Pagot translated from the French by John Wilding 1992 516pp ISBN 0 333 53818 8 published with Macmillan Press Ltd Available from CTA